Response to Levetiracetam Treatment and Long-Term Follow-Up in Dogs With Reactive Seizures Due to Probable Exogenous Toxicity - Stabile, Fabio; De Risio, Luisa (Frontiers in Veterinary Science, 2021)
Limited information is available on the long-term follow-up and seizure recurrence in dogs with reactive seizures due to suspected exogenous toxicity. The purpose of this study was to report the long-term follow-up of 13 dogs referred to a single referral hospital, diagnosed with reactive seizures and treated with a standardised levetiracetam protocol. All dogs received a loading levetiracetam dose of 60mg/kg/IV once, followed by a maintenance dose of 20mg/kg every 8 hours as part of an open-label clinical study. Levetiracetam was withdrawn after a 6-months seizure-free period by reducing levetiracetam to 20mg/kg every 12 hours for a 4-week seizure-free period, followed by levetiracetam 20mg/kg every 24 hours for a 4-week seizure-free period, before levetiracetam treatment was stopped. No adverse effects of the treatment were reported. No dogs experienced any seizures after discharge or after levetiracetam withdrawal. Median follow-up time from time of discharge was of 78months (=6years 6months). The result of this study supports the use of levetiracetam for treatment of reactive seizures due to exogenous substance intoxication. Moreover, our results do not support the need for long-term antiepileptic treatment in cases of reactive seizures due to exogenous intoxication.